INVESTIGATION OF THE TEMPERATURE REGIME OF THE TERRITORY OF THE SEMIPALATINSK POLYGON AND DESCRIPTION OF THE MATHEMATICAL MODEL AND ITS NUMERICAL SOLUTION - Marat Nurtas; Zh.D.Baishemirov (Academic Scientific Journal of Computer Science, 2019)
After the collapse of the Soviet Union, Kazakhstan inherited a very unpleasant legacy - the Semipalatinsk test site, where 456 nuclear explosions were made for 45 years [1]. Nuclear explosions formed on the ground long-term radioactive contamination in the form of long strips, the so-called "radioactive traces" that go far beyond the site [2]. Explosive mixtures especially led to numerous changes, including fire. The Relevance of the article is that despite the fact that the Semipalatinsk test site is closed, the heat distribution around the source of nuclear waste is preserved hence there is the need to study the temperature variation around the waste. This article reflects the change in the ambient temperature of nuclear waste that has been affected by nuclear explosions. As a basis for the article, we examined the effect of a small iron piece exposed to radiation and its effect on the temperature of the environment itself. The problem considers a mathematical model of a two-dimensional heat parabolic type equation and the value of initial and boundary conditions, as well as its numerical solution and a graphical representation of the same numerical solution. The result of this article is to demonstrate how accurately the environment exposed to radiation can be used for production or otherwise, and how to calculate a digital solution in the form of mathematical models and graphically illustrate a numerical solution.